Odpowiedzi

  • Użytkownik Zadane
2010-02-23T15:31:41+01:00
(x+y)+3/2(x-y)=24 /*2
1/3(x+y)+(x-y)=12 /*3

2x+2y+3x-3y=48
x+y+3x-3y=36

5x-y=48
4x-2y=36 /:(-2)

5x-y=48
-2x+y=-18
3x=30
x=10

4x-2y=36
-2y=36-4x /:(-2)
y=2x-18
y=2*10-18
y=2


x=10
y=2
2010-02-23T15:39:02+01:00
1(x+y)+1½(x-y)=24
⅓(x+y)+1(x-y)=12

x+y+1½x-1½y=24
⅓x+⅓y+x-y=12

2½x-½y=24 /×2
1⅓x-⅔y=12 /×3

5x-y=48 /×(-2)
4x-2y=36 (nr 1)

-10x+2y=-96
4x-2y=36
__________
-10x+2y+4x-2y=36-96
-6x=-60 /:(-6)
x=10 (nr 2)

nr 2 wst. do 1
4×10-2y=36
40-2y=36
-2y=-4/:(-2)
y=2
UKŁAD OZNACZONY (10;2)